Clinical, cultural and psychosocial impediments to self reporting of erectile dysfunction by men in Edo state, Nigeria - E. Irekpita (African Journal of Urology, 2017)
Introduction: Organic ED is presently considered as vasculogenic in the majority of affected middle age and elderly men and a sentinel event for cardiovascular disease. When men present with ED, it is advised that the opportunity should be used to assess their cardiovascular health. Objective: To determine the impediments to self reporting of ED and to assess the help seeking habits of men in Edo state with regards to ED. The secondary objective is to evaluate how acceptable sexual assessment is to these men when they present. Subjects and methods: This is a cross sectional study using a multi-facet, questionnaire with a section consisting of the international index of erectile function (IIEF). All men above 30 years who consented were included. Results: The response rate was 71.1%. The mean IIEF score was 20.33 with standard deviation of 4.656. The overall prevalence of ED was 51.2. Three hundred and eight of the respondents (33.3%) did not know where ED is treated, 273 (29.5%) thought that it is treated by complementary and alternative medicine practitioners while 237 (25.6) opted for the hospital as a point of care. This had a statistically significant correlation with location of the respondent (P = 0.000), level of education (P = 0.000) and senatorial zone (P = 0.000). Sexual evaluation was acceptable to 384 (41.5%) respondents when men present without ED and 757 (81.8%) when ED has occurred. This had a statistically significant correlation with level of education (P = 0.000), alcohol consumption (P = 0.000) and senatorial zone (P = 0.000). Conclusions: ED is highly prevalent in this community. Alcohol consumption, low educational level, ignorance of who and where ED is treated, location of respondent (rural) indifference, presence of co-morbidities and tribal beliefs appear to be associated with low self reporting. Affected men are more likely to patronize complementary and alternative medicine (CAM) practitioners than medical practitioners or may be out rightly indifferent. Acceptability of sexual evaluation of men is low when ED is absent and high when it has occurred.